2017
DOI: 10.1177/1524838017697308
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Self-Reported Elder Abuse Among Older Women in Community Settings: A Systematic Review and Meta-Analysis

Abstract: The abuse of older women appears to be a significant problem. Developing a better understanding of the extent of the problem is an important step toward preventing it. We conducted a global systematic review and meta-analysis of existing prevalence studies, in multiple languages, that occurred in the community settings from inception to June 26, 2015, in order to determine the extent of abuse against women aged 60 years and over. To disentangle the wide variations in prevalence estimates, we also investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 44 publications
1
43
0
8
Order By: Relevance
“…Additionally, our data extraction method for the quality assessment was not formally validated, but we adopted an approach similar to that used elsewhere [32,35,45] considering key variables in detail. Similarly, while there were no previously validated risk of bias measures for this specific type of prevalence study, we used a method with high interrater agreement that has been used elsewhere [45], including in prevalence studies of abuse and interpersonal violence [105][106]. Our approach to risk of bias adopted a conservative approach, and reasonably concluded that studies scoring 9.5 or 10 had minimal bias.…”
Section: Limitationsmentioning
confidence: 99%
“…Additionally, our data extraction method for the quality assessment was not formally validated, but we adopted an approach similar to that used elsewhere [32,35,45] considering key variables in detail. Similarly, while there were no previously validated risk of bias measures for this specific type of prevalence study, we used a method with high interrater agreement that has been used elsewhere [45], including in prevalence studies of abuse and interpersonal violence [105][106]. Our approach to risk of bias adopted a conservative approach, and reasonably concluded that studies scoring 9.5 or 10 had minimal bias.…”
Section: Limitationsmentioning
confidence: 99%
“…(Yon et al 2017: 9)This illustrates the overlap between IPV and elder abuse. Yon et al (2017: 9) subsume IPV in older women into elder abuse, and note that: ‘it is plausible that with increasing age, intimate partners are less physically capable of perpetrating the more “traditional” forms of IPV (i.e., physical and sexual)’.…”
Section: Introductionmentioning
confidence: 98%
“…Ironically, little research has been conducted to understand the relationship between elder abuse and DA, and existing reports mainly consider women as victims and men as perpetrators. Yon et al (2017), in a systematic review and meta-analysis, found a combined prevalence for overall elder abuse in the past year of 14.1 per cent. They argue that: Few research studies have compared abuse of women across age groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Una revisiĂłn sistemĂĄtica a partir de 50 estudios seleccionados publicados en varios idiomas de abusos autorreferidos por parte de personas mayores de 60 años que viven en el mundo comunitario, destaca que 1 de cada 6 personas es vĂ­ctima de abuso (14.1%). El abuso psicolĂłgico aparecerĂ­a en el 11.8% de los casos, las negligencias en el 4.1%, los econĂłmicos en el 3.8%, el sexual en el 2.2% y otras formas de abuso fĂ­sico en el 1.9% (21).…”
unclassified